Women’s health-related vulnerabilities in natural disasters: a systematic review protocol - Syadani Riyad Fatema; Md. Shahidul Islam; Leah East; Kim Usher (BMJ Open)
Introduction There is a paucity of evidence identifying both the physical and psychological health risks and underlying causes of women’s health-related vulnerabilities related to natural disasters. Therefore, this systematic review will be conducted to determine the impact of natural disasters on women’s health from a global perspective.Methods and analysis Five electronic databases of health research, including ProQuest, ProQuest Health and Medicine, PubMed, PsycINFO and CINAHL, will be searched to retrieve relevant literature where Medical Subject Headings terms and keywords will be used depending on the search method of each database. Google Scholar will also be searched for preliminary information on the topic and to check for further evidence that may have been missed. Inclusion and exclusion criteria will be developed and refined by the research team. We will restrict our search for empirical full-text articles published in the English language peer-reviewed journals between July 2008 and June 2018 to ensure contemporary evidence is retrieved. Two authors will participate in each step in the process, including title, abstract and full-text screening against inclusion criteria, data extraction and quality appraisal. The quality of selected studies will be assessed using the Mixed Method Appraisal Tool. Data synthesis will follow a sequential explanatory approach. Finally, the quantitative and qualitative findings will be merged under themes and described using a narrative approach.Ethics and dissemination Formal ethical approval is not required as primary data will not be collected. The results will be published in an international peer-reviewed journal and presented at national and international conferences.PROSPERO registration number CRD42019123809.